2017
DOI: 10.1177/0394632017709917
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular rehabilitation in benign paroxysmal positional vertigo: Reality or fiction?

Abstract: The objective of this article is to systematically review the evidence on the effectiveness of vestibular rehabilitation (VR) in patients with benign paroxysmal positional vertigo (BPPV). Relevant published studies about VR in BPPV were searched in PubMed, Google Scholar and Ovid using various keywords. We included trials that were available in the English language and did not apply publication year or publication status restrictions. Studies based on the VR in other peripheral and/or central balance disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
0
12
0
4
Order By: Relevance
“…Aunque en la actualidad se acepta que el tratamiento gold standard del VPPB son las maniobras de reposición canalicular, algunos pacientes manifiestan en las semanas posteriores a su recuperación con este tratamiento, síntomas de mareo e inestabilidad persistente sin nistagmo ni sensación vertiginosa en posiciones estáticas o dinámicas posiblemente en relación con la alteración de la información propioceptiva y visual [28,29]. La aparición de este cuadro se ha relacionado con factores tales como la edad, el tiempo de evolución del cuadro de VPPB [30,31] o con un componente de ansiedad.…”
Section: Inestabilidad Residual Tras El Vértigo Posicional Paroxísticunclassified
See 1 more Smart Citation
“…Aunque en la actualidad se acepta que el tratamiento gold standard del VPPB son las maniobras de reposición canalicular, algunos pacientes manifiestan en las semanas posteriores a su recuperación con este tratamiento, síntomas de mareo e inestabilidad persistente sin nistagmo ni sensación vertiginosa en posiciones estáticas o dinámicas posiblemente en relación con la alteración de la información propioceptiva y visual [28,29]. La aparición de este cuadro se ha relacionado con factores tales como la edad, el tiempo de evolución del cuadro de VPPB [30,31] o con un componente de ansiedad.…”
Section: Inestabilidad Residual Tras El Vértigo Posicional Paroxísticunclassified
“…Aunque la inestabilidad en la edad avanzada puede ser atribuida a múltiples causas, se estima que cerca de la mitad de los casos presenta una alteración vestibular [28]. En la búsqueda de factores que determinen cuáles de estos pacientes son subsidiarios de rehabilitación vestibular, Rossi y cols (2009) [32] encuentran un factor pronóstico de buena respuesta en aquellos pacientes con los límites de estabilidad alterados y peor en aquellos con la prueba Up and go alargado.…”
Section: Presbivértigounclassified
“…The best practice in treating BPPV is the Canalith Repositioning Procedure (CRP), and depending on the affected canals, different maneuvers have been described. 5 Almost 85% to 95% of cases of BPPV arise in the posterior semicircular canal (PC-BPPV). 6 To treat PC-BPPV, the Epley and Semont maneuvers are commonly used, with nearly similar success rates.…”
Section: Introductionmentioning
confidence: 99%
“…This review supports the contention that the primary intervention for BPPV should be CRP that directly treat the condition, but movement/habituation-based VR will further aid and benefit long-term functional recovery. A more recent review by Bressi et al 31 proposed that a hierarchy of interventions should be offered to patients with BPPV, starting with CRP and followed by post-treatment exercises. The findings also indicated that CRP and VR seem to have a synergic effect in patients with BPPV 31…”
Section: Introductionmentioning
confidence: 99%
“…A more recent review by Bressi et al 31 proposed that a hierarchy of interventions should be offered to patients with BPPV, starting with CRP and followed by post-treatment exercises. The findings also indicated that CRP and VR seem to have a synergic effect in patients with BPPV 31…”
Section: Introductionmentioning
confidence: 99%